Conceptual perspective of self-marketing Search descriptive - جثير سعدون حمود; سعيد سارة علي (Journal of Economics and Administrative Sciences, 2018)
Basic orientation is to look at identifying conceptual perspective to market self-research and descriptive, as has the marketing theme for the same attention in the practical side before endo scopic In recent years, is marketing an integrated and holistic included many areas not limited to the marketing of goods and services, and even included the marketing of religion, politics and individuals for themselves, as the awareness and concepts that seep into the soul of man from its inception until his arrival to the stage of owning a level of skills or expertise, scientific or all of those things degrees mixed with ambition and aspiration for self-realization takes way to search for opportunities or created, often observe individuals Amataron other news activities and job positions and what their lectures and participated in it from the seminars and what they have published books and what assets they have the skills, expertise and functional achievements, and continue to talk about themselves and reading achievement and attitudes heroic and creative, as if talking about the self is only one of the mechanisms used by a lot with a view to marketing themselves, and celebrities and politicians use marketing profile in the context of individuals described to take responsibility for marketing themselves for the purpose of maintaining the public relations industry, are widely used in contrast, the marketing of the same is also meant to create your own individual brand, and in this framework research aims to achieve Mrtkzan fought the first in a display intellectual philosophical implications of dialectics and consensus and differences in views on the variable current research and the marketing of the same based on the literature seriously by Alvkraladarei generally thought catalog, in particular through the previous intellectual efforts and proposals humble researcher, and Alankhrt evaluation of the possibility of adopting those levels and use them in programs and marketing related activities, while the targeted concentration and the second, which the body of the product and ambitious, in relation to Balnteg has the goal to provide a range conclusions, either ambition has targeted an attempt to urge the reader to develop cognition and awareness of the nature and application of marketing with search and seeking to deepen this awareness and how to benefit from the findings of the research results and concluded that such a view to making recommendations.